أثر المسرعات الحكومية في ارتفاع نسبة الطلاق بدولة الإمارات العربية المتحدة: The impact of government accelerators on the high divorce rate in the United Arab Emirates - Alblooshi, Hessa Ahmed Juma; Ahmad Wifaq bin Mokhtar, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث تهدف الدراسة إلى الكشف عن أثر المسرعات الحكومية في دولة الإمارات العربية المتحدة في ارتفاع نسبة الطلاق بين العائلات الإماراتية، كما تهدف الدراسة إلى فحص أهم الدوافع والأسباب المؤدية لإرتفاع نسبة الطلاق في المجتمع الإماراتي، في ظل المسرعات الحكومية بدولة الإمارات العربية المتحدة، والآثار المترتبة على إرتفاع تلك الظاهرة بين العائلات الإماراتية. وقد إعتمدت الدراسة على المنهج الوصفي التحليل في جانبة النظري. وإعتمدت الدراسة في جمع المعلومات وإستخلاص النتائج على أداة (المقابلة)، وتتكون أفراد عينة البحث الذين جرى معهم المقابلة من (10) حالات من المطلقات، وقد اتسمت العينة أنها (عينة عمدية غير عشوائية) من أجل التوصل إلى نتائج موثوقة، وقد توصلت نتائج الدراسة إلى مجموعة من النتائج من أهمها أنه أثر عمل المرأة الإماراتية في ظل المسرعات الحكومية على زيادة مظاهر التفكك الأسري، وزيادة نسبة الطلاق، لعدم تكيف العلاقات الأسرية وعدم تأقلمها للتغير الذي طرأ على أدوار أعضاء الاسرة وعلى مراكزهم. فلم يعد الطلاق يهم المرأة العاملة ولا يشكل أية عقبة تجاهها كما كان في السابق، كما بينت أنه ظل نجاح المرأة العاملة في ظِل المسرعات الحكومية ينجم عنه مشكلات أسرية مختلفة ناتج عن خروج الزوجة وخاصة الأم من المنزل للعمل، وهذه المشكلات تنعكس على الأبناء والزوج مما يؤثر على الإستقرار الأسري، واتضح أن زيادة قدرة المرأة على الكسب هي نتيجة لارتفاع معدلات الطلاق، كما بينت النتائج أن إرتفاع المستوى التعليمي سببا في رغبة المرأة في استقلالها في حياتها حتى لا تعرقلها القيود الأسرية في إستكمال مسيرة نجاحها المهني. وبينت نتائج الدراسة أن النساء اللاتي حصلن على ترقيات كن أكثر عرضة للطلاق مقارنة بزملائهن الأقل في الدرجة الوظيفية، وعليه اتضح أن الاستثمار في عمل المرأة يزيد رغبتها في العمل ويحد من رغبتها في الزواج مرة أخرى. وقد أوصت الدراسة ضرورة دراسة الأسباب المؤدية إلى زيادة حالات الطلاق، وضرورة تكاتف مؤسسات الدولة كافة، خصوصاً وسائل الإعلام المختلفة، للتعاون معاً في توعية أفراد المجتمع بالآثار السلبية للطلاق. ABSTRACT This paper aims to look into the impact of government accelerators in the United Arab Emirates with regards to the increase in the divorce rate among Emirati families. The study also aims to examine the main causes leading to the increase in the divorce rate in Emirati society, in light of government accelerators in the United Arab Emirates, and the effects of this phenoninal increase among Emirati families. The study relied on the descriptive analysis method in its theoretical aspect. In collecting information and drawing conclusions, the study relied on the (interview) tool. It samples individuals who were interviewed consisted of 10 cases of divorced women. The sample was characterized as (a non-random, intentional sample) in order to reach reliable results. The main findings of this study is that the impact of Emirati women’s work under government accelerators on the family break up, and increasing the divorce rate, due to the lack of adaptation of family relations and their failure to adapt to the change that occurred in the roles and positions of family members. Divorce is no longer concerns of working women and is not considered as any obstacle to them as it was in the past. She also showed that the success of working women under government accelerators lead to various family problems with regards to the wife, especially the mother, leaving the home to work, and these problems affect the children and husband, and also affect the family stability, it became clear that women's increased ability to earn is a result of high divorce rates. The study also shows that the high educational level is a reason for women's desire for independence in their lives so that family restrictions do not hinder them in completing their professional success path. The study also shows that women who receive promotions were more likely to divorce compared to their colleagues who were lower in job grade. Therefore, it became clear that investing in a woman’s career increases her desire to work and reduces her desire to marry again. The study recommends the need to study the reasons leading to an increase in divorce cases, and the need for all state institutions to join forces, especially the various media outlets, to cooperate together in educating members of society about the negative effects of divorce.